Geochemical characteristics of the primary halo in boreholes and prospecting prediction of the Banchang Cu-Mo polymetallic deposit in Henan Province - Juan Yao; Xiaoxu Zhang; Shengyuan Lu; Lei Chen; Lei Qin (地质科技通报, 2023)
The Banchang Cu-Mo polymetallic deposit is located in the middle section of the Zhuyangguan-Xiaguan regional fault, the North Qinling fold belt of the eastern Qinling orogenic belt. It is the first large copper deposit discovered in Henan Province. In the presurvey and general prospecting, a drilling workload of 23 600 meters was invested successively, extending the prospecting depth of the copper belt in Banchang by nearly kilometers, and the maximum thickness of the main ore body is 285.95 m. By systematical samples from 23 drilling holes of the No.220 to No.76 exploration line in the Banchang Cu-Mo polymetallic deposit, the primary halo characteristics were preliminarily studied. The geochemical primary halo obtained from the No.172 exploration line with the most construction drilling holes reveal the fluid transport channels. The study confirmed the zoning characteristic of fluid migration and mineralization-"Cu first and then Mo", and the vertical primary superimposed halo established by the Gregorian zoning index method is Sb-AS-Pb-Bi-Zn-Ag-Sn-Cu-W-Au-Mo in the mining area. Combined with the spatial distribution of ore bodies in the No.172 exploration line, four zonal indexes were further established as indicators for evaluating the spatial location of concealed ore bodies. All these factors provide a geochemical basis for deep prospecting.